Implementation of internet-delivered cognitive behavior therapy within community mental health clinics: a process evaluation using the consolidated framework for implementation research - H.D. Hadjistavropoulos; M.M. Nugent; D. Dirkse; N. Pugh (BMC Psychiatry, 2017)
Abstract Background Depression and anxiety are prevalent and under treated conditions that create enormous burden for the patient and the health system. Internet-delivered cognitive behavior therapy (ICBT) improves patient access to treatment by providing therapeutic information via the Internet, presented in sequential lessons, accompanied by brief weekly therapist support. While there is growing research supporting ICBT, use of ICBT within community mental health clinics is limited. In a recent trial, an external unit specializing in ICBT facilitated use of ICBT in community mental health clinics in one Canadian province (ISRCTN42729166; registered November 5, 2013). Patient outcomes were very promising and uptake was encouraging. This paper reports on a parallel process evaluation designed to understand facilitators and barriers impacting the uptake and implementation of ICBT. Methods Therapists (n = 22) and managers (n = 11) from seven community mental health clinics dispersed across one Canadian province who were involved in implementing ICBT over ~2 years completed an online survey (including open and closed-ended questions) about ICBT experiences. The questions were based on the Consolidated Framework for Implementation Research (CFIR), which outlines diverse constructs that have the potential to impact program implementation. Results Analyses suggested ICBT implementation was perceived to be most prominently facilitated by intervention characteristics (namely the relative advantages of ICBT compared to face-to-face therapy, the quality of the ICBT program that was delivered, and evidence supporting ICBT) and implementation processes (namely the use of an external facilitation unit that aided with engaging patients, therapists, and managers and ICBT implementation). The inner setting was identified as the most significant barrier to implementation as a result of limited resources for ICBT combined with greater priority given to face-to-face care. Conclusions The results contribute to understanding facilitators and barriers to using ICBT within community mental health clinics and serve to identify recommendations for improving uptake and implementation of ICBT in clinic settings.